Performance of doulas in the public health service - Géssica Larissa Barbosa Rocha; Mônica Cecília Pimentel de Melo; Sílvia Raquel Santos de Morais; Khesia Kelly Cardoso Matos (Universidade Federal de Santa Maria, 2020)
Objective: to analyze the performance of doulas in the public health service, based on their vision and management at a local maternity hospital. Method: qualitative, descriptive study, anchored in Martin Heidegger's existential phenomenological perspective, involving four doulas and three managers. In the data analysis, Discourse Analysis was used. Results: the fields of action of the doulas that emerged were primary care and hospital, and the main difficulty of action was the resistance of the medical team to accept this caregiver in the delivery scenario. The acquisition of information by professionals was presented by doulas as a possibility to mitigate the difficulties experienced in the hospital environment. The managers recognize the importance of the doula in the process of delivery and birth. Conclusion: The study provided an expanded view of the possibilities of doulas' performance in the public health service.